Interpersonal Stress Generation as a Mechanism Linking Rumination to Internalizing Symptoms in Early Adolescents - McLaughlin, Katie A. (2012)
Rumination is a risk factor for depressive and anxiety symptoms in adolescents. Previous investigations of the mechanisms linking rumination to internalizing problems have focused primarily on cognitive factors. We investigated whether interpersonal stress generation plays a role in the longitudinal relationship between rumination and internalizing symptoms in young adolescents. Adolescents (Grades 6–8, N =1,065) from an ethnically diverse community completed measures of depressive and anxiety symptoms, perceived friendship quality, and peer victimization at two assessments, 7 months apart. We determined whether rumination predicted increased exposure to peer victimization and whether changes in perceived friendship quality mediated this relationship. We also evaluated whether peer victimization mediated the association between rumination and internalizing symptoms. Adolescents who engaged in high levels of rumination at baseline were more likely to experience overt, relational, and reputational victimization at a subsequent time point 7 months later, controlling for baseline internalizing symptoms and victimization. Increased communication with peers was a significant partial mediator of this association for relational (z =1.98, p =.048) and reputational (z =2.52, p =.024) victimization. Exposure to overt (z = 3.37, p =.014), relational (z =3.67, p <.001), and reputational (z = 3.78, p < .001) victimization fully mediated the association between baseline rumination and increases in internalizing symptoms over the study period. These findings suggest that interpersonal stress generation is a mechanism linking rumination to internalizing problems in adolescents and highlight the importance of targeting interpersonal factors in treatment and preventive interventions for adolescents who engage in rumination.